Anxiety during pregnancy and preeclampsia: a case - control study - Masoumeh Kordi; Azra Vahed; Fariborz Rezaee Talab; Seyed Reza Mazloum; Marzieh Lotfalizadeh (Mashhad University of Medical Sciences, 2017)
Introduction:  Preeclampsia is the common and dangerous complication of pregnancy with unknown reason. Multiple causes such as depression, psychological and physical stress may be involved in its development. This study was performed to determine the relationship between anxiety during pregnancy and the incidence of preeclampsia. Methods: This case-control study was conducted on 150 pregnant women with preeclampsia and 150 healthy pregnant women referred to health centers and academic hospitals of Mashhad in 2014. The diagnosis of preeclampsia was made by systolic blood pressure ≥140 mm Hg or diastolic blood pressure ≥90 mm Hg accompanied with urinary protein excretion more than 300 mg per 24 hours. The cutoff point for the presence of anxiety was the score of ≥8; the score of 8-9 was mild anxiety and the score of 20 was very severe anxiety. Data collection tools included the form of demographic characteristics, clinical and laboratory signs of preeclampsia, and depression, anxiety, and stress scale (DASS 21). Data were analyzed using SPSS software (version 16) and independent t-test, Mann-Whitney, Chi-square, and logistic regressions model. P Results: We found significant relationship between anxiety and preeclampsia (P